Addressing molecular optomechanical effects in nanocavity-enhanced Raman scattering beyond the single plasmonic mode. Issue 3 (14th January 2021) - Zhang, Yuan; Esteban, Ruben; Boto, Roberto A.; Urbieta, Mattin; Arrieta, Xabier; Shan, ChongXin; Li, Shuzhou; Baumberg, Jeremy J.; Aizpurua, Javier
Abstract : A full multimodal description of a plasmonic cavity within a continuum-field model of molecular optomechanics provides new insights into vibrational dynamics and nonlinearities of Surface-Enhanced Raman Scattering (SERS). Abstract : The description of surface-enhanced Raman scattering (SERS) as a molecular optomechanical process has provided new insights into the vibrational dynamics and nonlinearities of this inelastic scattering process. In earlier studies, molecular vibrations have typically been assumed to couple with a single plasmonic mode of a metallic nanostructure, ignoring the complexity of the plasmonic response in many configurations of practical interest such as in metallic nanojunctions. By describing the plasmonic fields as a continuum, we demonstrate here the importance of considering the full plasmonic response to properly address the molecule-cavity optomechanical interaction. We apply the continuum-field model to calculate the Raman signal from a single molecule in a plasmonic nanocavity formed by a nanoparticle-on-a-mirror configuration, and compare the results of optomechanical parameters, vibrational populations, and Stokes and anti-Stokes signals of the continuum-field model with those obtained from the single-mode model. Our results reveal that high-order non-radiative plasmonic modes significantly modify the optomechanical behavior under strong laser illumination. Moreover, Raman linewidths, lineshifts, vibrational populations, and parametric instabilities are found to be sensitive to the energy of the molecular vibrational modes. The implications of adopting the continuum-field model to describe the plasmonic cavity response in molecular optomechanics are relevant in many other nanoantenna and nanocavity configurations commonly used to enhance SERS.